RGFP966 inhibits activation of AIM2 inflammasomes to promote mitophagy to relieve acute gouty arthritis - Zewei Wang; Chunyang Liu; Feng Cheng; Xiuyun Shi; Jing Dai; Jing Tian; Hongxu Jin; Ying Liu (PLoS ONE, 2026)
Acute gouty arthritis (AGA) is a common inflammatory joint disease characterized by pain resulting from the deposition of monosodium urate (MSU) crystals into joints and surrounding tissues. RGFP966, a selective inhibitor of histone deacetylases 3 (HDAC3), can down-regulate the AIM2 inflammasomes. This study aimed to explore the mechanism of action of RGFP966 in MSU-induced AGA. MSU-induced AGA rats were treated with RGFP966 or colchicine, and physiological and pathological indicators were determined. The rat joint synovial tissues and kidneys pathological damage was observed by hematoxylin and eosin staining. Enzyme-linked immunosorbent assay (ELISA), Western blot, JC-1 staining, mitochondrial membrane potential (MMP) measurement, ATP assay, and immunofluorescence were applied to evaluate the effects of RGFP966 on the AIM2 inflammasomes and mitophagy. In MSU-induced AGA rats, RGFP966 significantly improved the gait score, the swelling degree and synovitis score. In addition, RGFP966 repressed the increased serum levels of IL-1β, IL-18, IL-6 and TNF-α, and reduced the protein levels of AIM2, Pro-caspase-1, Cleaved-caspase-1, ASC, Pro-IL-1β, and Cleaved-IL-1β in MSU-induced AGA rats. Furthermore, RGFP966 decreased the level of reactive oxygen species (ROS), increased the level of ATP and MMP, and promoted the levels of Pink1, Parkin and LC3-II. Collectively, RGFP966 significantly alleviated AGA, and the underlying mechanism is related to promote mitophagy by inhibiting the activation of the AIM2 inflammasomes.